2019
DOI: 10.26434/chemrxiv.7903388.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimally Empirical Double Hybrid Functionals Trained Against the GMTKN55 Database: revDSD-PBEP86-D4, revDOD-PBE-D4, and DOD-SCAN-D4

Abstract: We present a family of minimally empirical double-hybrid DFT functionals parametrized against the very large and diverse GMTKN55 benchmark. The very recently proposed wB97M(2) empirical double hybrid (with 16 empirical parameters) has the lowest WTMAD2 (weighted mean absolute deviation over GMTKN55) ever reported at 2.19 kcal/mol. However, our xrevDSD-PBEP86-D4 functional reaches a statistically equivalent WTMAD2=2.22 kcal/mol, using just a handful of empirical parameters, and the xrevDOD-PBEP86-D4 functional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(134 citation statements)
references
References 22 publications
6
128
0
Order By: Relevance
“…194 Because, as Goerigk and Grimme noted, "DHDFs still suffer from the same 'missing dispersion energy problem' as other functionals, albeit to a smaller extent, and consequently they do also benefit from dispersion-correction schemes" 52 they added a dispersion correction to the available double-hybdrid functionals, and subsequently this was done in a more intrinsic manner by Kozuch and Martin in their DSD-BLYP and subsequent related functionals. 20,[144][145][146] Thus, it would seem that including a dispersion correction is recommended also for doublehybrid functionals. PWPB95 without any dispersion correction has the lowest MAD (1.6 kcal/mol) of all the DFT functionals evaluated, while B2K-PLYP is only slightly worse (MAD = 1.7…”
Section: Performance Of Dft Functionals Against the Mobh35 Databasementioning
confidence: 99%
See 1 more Smart Citation
“…194 Because, as Goerigk and Grimme noted, "DHDFs still suffer from the same 'missing dispersion energy problem' as other functionals, albeit to a smaller extent, and consequently they do also benefit from dispersion-correction schemes" 52 they added a dispersion correction to the available double-hybdrid functionals, and subsequently this was done in a more intrinsic manner by Kozuch and Martin in their DSD-BLYP and subsequent related functionals. 20,[144][145][146] Thus, it would seem that including a dispersion correction is recommended also for doublehybrid functionals. PWPB95 without any dispersion correction has the lowest MAD (1.6 kcal/mol) of all the DFT functionals evaluated, while B2K-PLYP is only slightly worse (MAD = 1.7…”
Section: Performance Of Dft Functionals Against the Mobh35 Databasementioning
confidence: 99%
“…Finally, a wide variety of DFT functionals was evaluated to determine which perform well, ideally for both thermodynamics (i.e., MOR41) and kinetics (i.e., MOBH35). As part of this study, MOR41 was used to evaluate some of the newer functionals that were not part of Dohm et al's original study, including the latest functionals from the Martin (the revised DSD/DOD double-hybrid functionals 20 ), Truhlar (e.g., MN15, 21 MN15-L 22 ) and Head-Gordon (e.g., ωB97M-V, 23 B97M-V 24 ) groups.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this level of theory has been denoted as B3. More accurate structures and harmonic zero-point energies of the low-lying energy minima have then been obtained using the double-hybrid revDSD-PBEP86-D3(BJ) functional [ 53 ] in conjunction with the jun-cc-pVTZ (jTZ) basis set [ 54 ] (this level of theory has been denoted as rDSDjun). From a spectroscopic point of view, while equilibrium geometries straightforwardly provide equilibrium rotational constants, the prediction of the vibrational ground-state rotational constants requires the incorporation of vibrational corrections, which have been obtained from anharmonic force field calculations at the B3 level (for a detailed account, see e.g., ref.…”
Section: Methodsmentioning
confidence: 99%
“… 47 In DHDFT, both the exchange and the correlation terms are mixtures of DFT and WFT approaches (evaluated in a basis of Kohn–Sham orbitals). Using the very large GMTKN55 (general main-group thermochemistry, kinetics, and noncovalent interactions, 55 subsets) benchmark suite, 48 with nearly 2500 main-group molecules, we found that the best DHDFT functionals, ωB97M(2) by Mardirossian and Head-Gordon 49 and revDSD-PBEP86-D4 by our group, 45 have WTMAD2 (weighted mean absolute deviation) statistics around 2.2 kcal/mol, competitive with or superior to the cWFT methods we tested. Needless to say, double hybrids are computationally much more economical, especially if RI (resolution of the identity) approximations 50 52 are applied.…”
Section: Introductionmentioning
confidence: 94%
“…An approach that, in practical operation, combines elements of WFT and DFT methods is the double-hybrid density functional method (DHDFT, 40 45 see ref ( 46 ) for a recent review), which occupies the fifth rung on Perdew’s “Jacob’s Ladder”. 47 In DHDFT, both the exchange and the correlation terms are mixtures of DFT and WFT approaches (evaluated in a basis of Kohn–Sham orbitals).…”
Section: Introductionmentioning
confidence: 99%